2022
DOI: 10.1097/spv.0000000000001276
|View full text |Cite
|
Sign up to set email alerts
|

Supraphysiologic Vaginal Estrogen Therapy in Aged Mice Mitigates Age-Associated Bladder Inflammatory Response to Urinary Tract Infections

Abstract: Importance Bladder diseases characterized by chronic inflammation are highly prevalent in older women, as are recurrent urinary tract infections (rUTIs). Recurrent urinary tract infections lead to chronic inflammation of the bladder mucosa and cause lower urinary tract symptoms that persist even after the infection is cleared. Vaginal estrogen therapy (VET) has long been used for the treatment of rUTIs; however, its mechanism of action remains unclear.Objectives The objective of this study was to examine the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 84 publications
(190 reference statements)
0
1
0
Order By: Relevance
“…12,13 Recent work from our group shows that vaginal estrogen therapy in old female mice appears to promote regression of these CC/TLT lesions in part by reducing levels of TLT-promoting chemokines. 14 Our study in postmenopausal women showed that antibiotics were associated with relatively rapid CC resolution. This is consistent with findings from De Nisco et al showing presence of TLTs associated with diverse bacterial species in bladder biopsy samples from postmenopausal women with rUTIs undergoing cystoscopy, 15 and from Crivelli et al 16 and Ordonez et al 17 showing electrofulguration by cauterization of CC/TLT led to improved outcomes in women with antibiotic-refractory rUTIs.…”
Section: Discussionmentioning
confidence: 64%
“…12,13 Recent work from our group shows that vaginal estrogen therapy in old female mice appears to promote regression of these CC/TLT lesions in part by reducing levels of TLT-promoting chemokines. 14 Our study in postmenopausal women showed that antibiotics were associated with relatively rapid CC resolution. This is consistent with findings from De Nisco et al showing presence of TLTs associated with diverse bacterial species in bladder biopsy samples from postmenopausal women with rUTIs undergoing cystoscopy, 15 and from Crivelli et al 16 and Ordonez et al 17 showing electrofulguration by cauterization of CC/TLT led to improved outcomes in women with antibiotic-refractory rUTIs.…”
Section: Discussionmentioning
confidence: 64%